Effective power and effective power density analysis for water in diesel emulsion as fuel in diesel engine performance - Rai R.K.; Sahoo R.R. (My University, 2025)
In the present theoretical study, a comparative performance analysis of a single cylinder compression ignition engine with diesel, 5% and 10% water in diesel emulsion as fuels have been investigated. Effect of variation in engine operating parameters like inlet pressure, friction coefficient compression ratio, equivalence ratio, and a residual gas fraction on engine performance parameters, i.e., effective power, effective power density, and total heat loss have been analyzed. Analysis has been carried out on the basis of isobaric heat addition and isochoric heat rejection assumptions with temperature variable specific heats and composition of alternative fuels. Microexplosion phenomenon for secondary atomization in water in diesel emulsion fuels improves the fuel combustion efficiency for better performance. The theoretical analysis revealed that the effective power and effective power density for diesel fuel are found to be increased by 14.4% and 28.6% respectively, compared to 5% and 10% water in diesel emulsion fuels in compression ignition engine at 1 bar inlet pressure. Highest effective power and effective power density are obtained with an equivalence ratio of 1.2 for all mentioned fuels. Increase in inlet pressure results in increase effective power, effective power density, and total heat loss performances. Highest effective efficiency has been found with an equivalence ratio of 0.89 for diesel, 5% and 10% water in diesel emulsion fuels and is highly affected by inlet pressure for all mention fuel type. Also, an increase in friction coefficient and residual gas fraction decreases effective power, effective power density and effective efficiency for diesel, 5% and 10% water in diesel emulsion fuels. Obtained results are an essential tool for compression ignition engine designer and also provoked to use the water in diesel emulsion fuels as an alternative fuel in place of neat diesel fuel. © 2019 Elsevier Ltd